Changing molecular epidemiology of rotavirus infection after introduction of monovalent rotavirus vaccination in Scotland. Issue 1 (3rd January 2017) - Mukhopadhya, Indrani; Murdoch, Heather; Berry, Susan; Hunt, Alison; Iturriza-Gomara, Miren; Smith-Palmer, Alison; Cameron, J. Claire; Hold, Georgina L.
Highlights: Rotarix® was included in the childhood immunisation schedule from June 2013 in Scotland. Significant drop in rotavirus detection (74.4%) after the introduction of the vaccine was noted. The predominant pre-vaccination G1P[8] strain showed a rapid decrease (72.1–15%). There was a parallel increase of G2P[4] strains from 7.2% to 21.9% of all rotavirus cases. First report of rotavirus epidemiology in Scotland after introduction of Rotarix® vaccine. Abstract: Background: Rotaviruses (RV) are the leading cause of gastroenteritis in children less than five years of age worldwide. Rotarix®, a live attenuated monovalent vaccine containing a RV strain of G1P[8] specificity has been included in the childhood immunisation schedule from June 2013 in Scotland. This study aimed to characterise the prevalent RV strains in Scotland before and after the introduction of the RV vaccine. Methods: RV positive faecal samples from Scottish virology laboratories covering the years 2012–2015 were genotyped. Viral RNA was extracted from faecal suspensions. VP7 and VP4 gene specific primers were used for multiplex hemi-nested PCRs and sequencing. Mann-Whitney U test and Chi-square test were used for statistical comparison. Results: There was a decrease in RV positive samples from the Scottish virology laboratories from 7409 samples in the pre-vaccination years (2009–2013) to 760 in 2014–2015, with an annual reduction of RV infections by 74.4% (RR-3.95; 95%-CI, 3.53–4.42, p < 0.001). 362 samples from the pre-vaccination period and 278 samples from the post-vaccination were genotyped. There was a drop in prevalence of G1P[8] strains (72.1%, 95%-CI, 67.42–76.33 to 15%, 95%-CI, 11.38–19.79) after introduction of the vaccine. In the post-vaccination period G2P[4] was the dominant strain in Scotland (21.9%, 95%-CI, 17.48–27.17) with increase in G9P[8] (12.9%, 95%-CI, 9.50–7.41), G12P[8] (12.2%, 95%-CI, 8.89–16.60) and G3P[8] (11.9%, 95%-CI, 8.58–16.20) infections. Phylogenetic analysis of the VP7 and VP4 genes showed no major differences between the pre and post-vaccination G1P[8] strains. Conclusion: This laboratory based surveillance study shows significant reduction in reported RV cases and a shift in proportion from G1P[8] to G2P[4] strains after introduction of RV vaccination in Scotland. The genotyping data from a subset of the total reported RV cases will be used to ascertain cross protection against strains and identify vaccine induced RV strain shifts in the years to come.